Integrated ground-based observing systems applications for climate, meteorology, and civil protection - Cimini, Domenico; Marzano, Frank S.; Visconti, Guido 1943- (Springer, 2011)
This book is a collection of the lectures delivered during the 7th International Summer School on Atmospheric and Oceanic Sciences (ISSAOS) titled 'Integrated Ground-Based Observing Systems Applications for Climate, Meteorology, and Civil Protection'. Its aim is to contribute to the scientific understanding of basic concepts and applications of integrated ground-based observing systems. The first part describes the most common instrumentations showing their strengths and limitations. Furthermore, strategic plans for the deployment of an observation site are discussed along with an overview of.